Fatores determinantes da estrutura de capital de pequenas e médias empresas de capital fechado: evidência empírica no cenário brasileiro no período de 2000 a 2007 - Rocha, Carlos Adriano (2009)
This study examines the capital structure of small and medium-sized enterprises in Brazil, specifically the determinants of total, short and long term debt ratios as well as determinants of onerous debt ratios. It used a database composed of 22,000 small businesses and 19,000 medium-sized enterprises, evaluated in a time frame of eight years (2000 to 2007) and compared the macroeconomic variable of the evolution of real GDP with the variable of time measured in years. Moreover, several factors were validated in the specialized literature as determinants of capital structure of companies. The technique used was econometrics models for panel data. The determinants of debt found in common was the profitability, the growth rate of assets, non-debt tax shields, age of firms and the risk of liquidity. On the other hand, vertical integration, capital source and partner risk did not seem to have an effect on the level of debt in small and medium firms. The rating variation and internationalization activity factors were introduced as capital structure determinants of these firms. In general terms, the results suggested that the Pecking Order Theory is more consistent to explain the capital structure of the Brazilian small and medium enterprises